The Role of Innate Lymphoid Cells in Immune-Mediated Liver Diseases - Liu, Meifang; Zhang, Cai (Frontiers in Immunology, 2017)
Innate lymphoid cells (ILCs) are a recently identified group of innate immune cells lacking antigen-specific receptors that can mediate immune responses and regulate tissue homeostasis and inflammation. ILCs comprise group 1 ILCs, group 2 ILCs, and group 3 ILCs. These ILCs usually localize at mucosal surfaces and combat pathogens by the rapid release of certain cytokines. However, the uncontrolled activation of ILCs can also lead to damaging inflammation, especially in the gut, lung, and skin. Although the physiological and pathogenic roles of ILCs in liver diseases have been attracting increasing attention recently, there has been no systematic review regarding the roles of ILCs in immune-mediated liver diseases. Here, we review the relationships between the ILC subsets and their functions in immune-mediated liver diseases, and discuss their therapeutic potential based on current knowledge about the functional roles of these cells in liver diseases.